Focus Group Discussion Penyelenggaraan Layanan Pendidikan Inklusif pada Guru KB TK Alam Efata Bersinar Salatiga - Trivena Dyah Wijayanti (Compromise Journal Community Proffesional Service Journal, 2024)
Inclusive education is an education service by including children with special needs and or experiencing obstacles in access to education to obtain quality education together with other students in general, but problems in the field are still found in the condition of institutions that do not have the availability of infrastructure, competent educators and support from parents who have children with special needs. This also happened at KB / TK Alam Efata Bersinar, so a community service activity was designed Focus Group Discussion (FGD) Implementation of Inclusive Education Services facilitated by the PG PAUD UKSW community service team to increase teachers' understanding and skills in preparing and implementing learning in inclusive classes to support the development of students, especially early childhood with special needs. The results of this activity were able to increase the average conceptual understanding of respondents with a percentage reaching 60% for all discussion topics and FGD material on the theme of organizing inclusive education provided